Carboxypeptidase B blocks ex vivo activation of the anaphylatoxin-neutrophil extracellular trap axis in neutrophils from COVID-19 patients - Yue Zhang; Kai Han; Chunjing Du; Rui Li; Jingyuan Liu; Hui Zeng; Liuluan Zhu; Ang Li (Critical Care, 2021)
Abstract Background Thrombosis and coagulopathy are highly prevalent in critically ill patients with COVID-19 and increase the risk of death. Immunothrombosis has recently been demonstrated to contribute to the thrombotic events in COVID-19 patients with coagulopathy. As the primary components of immunothrombosis, neutrophil extracellular traps (NETs) could be induced by complement cascade components and other proinflammatory mediators. We aimed to explore the clinical roles of NETs and the regulation of complement on the NET formation in COVID-19. Methods We recruited 135 COVID-19 patients and measured plasma levels of C5, C3, cell-free DNA and myeloperoxidase (MPO)-DNA. Besides, the formation of NETs was detected by immunofluorescent staining and the cytotoxicity to vascular endothelial HUVEC cells was evaluated by CCK-8 assay. Results We found that the plasma levels of complements C3 and MPO-DNA were positively related to coagulation indicator fibrin(-ogen) degradation products (C3: r = 0.300, p = 0.005; MPO-DNA: r = 0.316, p = 0.002) in COVID-19 patients. Besides, C3 was positively related to direct bilirubin (r = 0.303, p = 0.004) and total bilirubin (r = 0.304, p = 0.005), MPO-DNA was positively related to lactate dehydrogenase (r = 0.306, p = 0.003) and creatine kinase (r = 0.308, p = 0.004). By using anti-C3a and anti-C5a antibodies, we revealed that the complement component anaphylatoxins in the plasma of COVID-19 patients strongly induced NET formation. The pathological effect of the anaphylatoxin-NET axis on the damage of vascular endothelial cells could be relieved by recombinant carboxypeptidase B (CPB), a stable homolog of enzyme CPB2 which can degrade anaphylatoxins to inactive products. Conclusions Over-activation in anaphylatoxin-NET axis plays a pathological role in COVID-19. Early intervention in anaphylatoxins might help prevent thrombosis and disease progression in COVID-19 patients.